2019
DOI: 10.1002/ppap.201800152
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the pH value on the degradation of an azo dye of methyl orange by air discharge plasma

Abstract: Treatment of methyl orange (MO) synthetic wastewater by air discharge plasma was investigated, and the solution's pH value was found to be a key parameter of influencing the treatment efficiency. The results indicate that lower pH value can induce production of high reactive species, NO+ and peroxynitrous acid, which can contribute to the MO decomposition. When the appropriate amount of Fe2+ ions is present in the MO solution, the MO decomposition can be promoted by Fenton's reaction (Fe2+ reacts with H2O2 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Therefore, the reduction in bond energy under acidic conditions leads more easily to the decomposition of MO. 66,67…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the reduction in bond energy under acidic conditions leads more easily to the decomposition of MO. 66,67…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the reduction in bond energy under acidic conditions leads more easily to the decomposition of MO. 66,67 It was found that under alkaline conditions, MG was converted to colorless tertiary alcohol, resulting in the solution rapidly fading from blue-green to colorless. 68,69 Due to the limitations of the experimental conditions, absorbance cannot be tested, so only acid and neutral conditions were investigated.…”
Section: 22mentioning
confidence: 99%
“…The solution's properties in the PES such as the conductivity and the pH value are important for the efficiency of the PES applications. [23][24][25][26] In order to optimize the applications of the PES, better understanding of the influence of the solution's properties is necessary. In this paper, we investigate the Ag + reduction processes at different pH values in the PES with an aqueous solution of silver nitrate (AgNO 3 ), and the effects of these fundamental processes on the silver nanoparticle synthesis.…”
mentioning
confidence: 99%